Death Concern and Death Obsession in Iranian Nurses. Issue 3 (June 2015) - Dadfar, Mahboubeh; Lester, David
The goal of the present study was to examine whether nurses had increased death concern and death obsession compared to non-nursing staff. A Death Concern Scale and a Death Obsession Scale, translated into Persian, were administered to 56 female Iranian nurses (55% in their 30s) and compared to 56 female hospital staff members (45% in their 30s). The two groups did not differ significantly in their scores on either scale. It is, therefore, recommended that death education programs in hospitals be given to all staff, nursing and non-nursing.